Burkholderia thailandensis: Growth and Laboratory Maintenance. Issue 1 (12th August 2016) - Garcia, Erin C.; Cotter, Peggy A.
Abstract: Burkholderia thailandensis is a nonpathogenic Gram‐negative bacterium found in tropical soils. Closely related to several human pathogens, its ease of genetic manipulation, rapid growth in the laboratory, and low virulence make B. thailandensis a commonly used model organism. This unit describes the fundamental protocols for in vitro growth and maintenance of B. thailandensis in the laboratory. © 2016 by John Wiley & Sons, Inc.